PENGARUH KOMITMEN AFEKTIF TERHADAP LOYALITAS PEGAWAI PEMERINTAH NON PEGAWAI NEGERI (PPNPN) UNIT AVSEC (UPBU) BANDAR UDARA KELAS I DOMINE EDUARD OSOK SORONG PAPUA BARAT - Immanuel Danger Field Fonataba (Pusat Riset dan Inovasi Nasional, 2023)
The growth in the number of PPNPN at Domine Eduard Osok Airport is significantly higher than the number of civil servants. addition to balance effectiveness in the work environment of Class I Airport Domine Eduard Osok Sorong, West Papua. Affective commitment is a person's emotional attachment to work or organization. The existence of emotional attachment felt by Government Employees Non Civil Servants triggers the emergence of loyalty, where this loyalty has an impact on their desire to devote themselves to the agency. This study uses quantitative methods with a total of 30 respondents. The data collection technique uses a questionnaire which is distributed to the sample, namely Government Employees, Non-Civil Servants. In his confirmation, validity and reliability tests were carried out, simple linear regression tests, and the coefficient of determination using IBM SPSS Statistics 26. Based on the hypothesis regarding the effect of affective commitment on the loyalty of Government Employees Non Civil Servants, the calculated f value was 32,802 with a significance of 0,000 and from the results of the coefficient test determination to obtain a correlation value between variables of 0.734 and an r2 value of 0.539 or 53.9% and 46.1% which are influenced by other variables outside this study.